Green Technology and Vocational College: A Preliminary Study - Kaliappan, Anusuya; Hamid, Hashima (Online Journal for TVET Practitioners, 2022)
Green technology is an environmental technology and critical to the future of our society. Its main significance is to find the means to produce technology in ways that do not damage or deplete the Earth’s natural resources. Although, many studies have been conducted pertaining to green technology, but it remains unclear when it comes to the knowledge, attitude and practices of the students from vocational colleges in Malaysia. Therefore, the purpose of this study is to investigate the level of knowledge, attitude and practices regarding green technology among vocational colleges students. The study was conducted quantitatively using survey involving 183 students from 4 vocational colleges in Johor. A set of questionnaires was administered face to face and the data obtained were analysed using descriptive and inferential statistics such as frequency, percentage, mean, standard deviation, t-test and one-way ANOVA through Statistical Package for Social Science (SPSS) Version 23. The findings revealed the level of knowledge on green technology is average (mean=3.07), meanwhile level of attitude (mean=3.60) and practices on green technology (mean=4.00) are high among vocational colleges students. The findings also added that there is no significant difference in vocational colleges students’ education level with knowledge, attitude and practices of green technology. It also demonstrated that there is no significant difference in vocational colleges students’ undertaken courses with knowledge, attitude and practices of green technology. These findings are based on the notion that increasing knowledge will further influence behaviour change regarding green technology among vocational colleges students.  These vocational colleges students are the future skilled and semi-skilled workers in the country and are future generation and therefore it is obligatory to inculcate them with knowledge, attitude and practices of green technology.